An evaluation of echo in life support (ELS): is it feasible? What does it add?. Issue 2 (4th October 2010) - Hayhurst, C; Lebus, C; Atkinson, P R; Kendall, R; Madan, R; Talbot, J; Ross, P; Lewis, D
Abstract : Background: Emergency physicians were trained to perform echo in life support (ELS)—that is, limited transthoracic echocardiography during advanced life support (ALS) management of cardiac arrest. Methods: Data were collected on the adequacy of views obtained and timing of the scan, as well as the clinical findings of pericardial effusion and ventricular wall motion. Any intervention performed as a result of the scan was also noted. ELS was performed on 50 patients during cardiac arrest. Results: Adequate views were obtained in 47 (94%) scans, and 45 (90%) were obtained within the 10 s rhythm check. Twenty patients (40%) had ventricular wall motion (VWM), three (6%) had pericardial effusions and six patients (12%) had an intervention performed as a direct result of the scan. These included pericardiocentesis, thrombolysis and insertion of a chest drain. The presence of VWM had a positive predictive value of 55%. The absence of VWM resulted in a negative predictive value of 97% for predicting return of spontaneous circulation (ROSC). Conclusion: It is concluded that ELS is feasible and that the scan findings may guide further interventions.